2022
DOI: 10.3390/ijms232415882
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Octominin-Encapsulated Chitosan Nanoparticles Enhanced Antifungal and Antibacterial Activities

Abstract: Antimicrobial peptides (AMPs) have become a key solution for controlling multi-drug-resistant (MDR) pathogens, and the nanoencapsulation of AMPs has been used as a strategy to overcome challenges, such as poor stability, adverse interactions, and toxicity. In previous studies, we have shown the potent antimicrobial activity of Octominin against Candida albicans and Acinetobacter baumannii. This study is focused on the nanoencapsulation of Octominin with chitosan (CS) and carboxymethyl chitosan (CMC) as a drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The results of the release study agreed with the previous study reported by Jayathilaka et al ( 2022 ). The maximum cumulative release was 88.26% at 96 h using low-molecular-weight chitosan.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the release study agreed with the previous study reported by Jayathilaka et al ( 2022 ). The maximum cumulative release was 88.26% at 96 h using low-molecular-weight chitosan.…”
Section: Discussionsupporting
confidence: 92%
“…2021, 110, [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). As in the case of temporin B, the encapsulation of Octominin into the core-shell of CS-NPs resulted in the sustained release of Octominin over 96 h, causing higher biofilm inhibition and the eradication of C. albicans and Acinetobacter baumanii [ 113 ]. In addition, CS-NPs loaded with Octominin showed reduced toxicity in comparison to free Octominin both in vitro using human embryonic kidney 293 (HEK 293) cells and in an in vivo Zebrafish model.…”
Section: Applications Of Glycosylation and Lipidation To Improve Acti...mentioning
confidence: 99%
“… 32 Furthermore, higher antibacterial and antifungal activity against A. baumannii and C. albicans was observed when Octominin peptide was loaded into CNPs, as revealed by time–kill kinetic and microbial viability assays. 30 …”
Section: Discussionmentioning
confidence: 99%